The Effect of Work Attitude and Job Satisfaction on Employee Performance - Dzaky, Mohammad Faishal; Tara, Muhammad Faizin Ramadhan; Rhadiansyah, Muhammad Fauzan; Herlambang, Muhammad Sunan Maghribi; Triandra Putra, Muhammad Zaidan; Habiburohman, Roihan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Based on empirical results from various studies, this study is a systematic literature review aimed at analyzing the relationship between work attitudes and job satisfaction and employee performance. Work morale and job satisfaction are considered two important components of organizational behavior that can influence performance. However, the strength and mode of their influence can vary depending on the situation. The results indicate that a positive work attitude typically results in more responsible, collaborative, and quality-oriented work behavior. Furthermore, sustained job satisfaction improves performance by increasing employee motivation, commitment, and sense of organizational attachment. However, numerous supporting and inhibiting factors influence the influence of these two variables, which are contextual in nature. Good work discipline, good leadership, motivation, organizational justice, a conducive work environment, and competence can enhance the relationship between work attitudes and job satisfaction on performance. Conversely, excessive workload, work pressure, an unsupportive work environment, and task ambiguity can weaken the relationship. Overall, this study found that work attitudes and job satisfaction play a significant role in improving employee performance; however, the results are highly dependent on organizational conditions and other supporting factors in the workplace.